Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Body Serum Lavojoy Pada Platform Tiktok - Widiyati Jariyah; Rangga Dalu Aji Toana (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aims to determine and analyze the magnitude of the influence of product quality and priceon purchasing decisions for Lavojoy body serum products on the TikTok platform. The researchmethod used is a quantitative descriptive method. The population in this study were consumers whohad purchased Lavojoy body serum products through the TikTok Platform. The sampling techniqueused the Cochran formula with the probability sampling method, so that a sample size of 100respondents was obtained. The data analysis technique in this study uses descriptive statistics andmultiple linear regression analysis. This study uses instrument tests (validity and reliability), classicalassumption tests (normality, multicollinearity, and heteroscedasticity), and hypothesis tests (t-test,f-test, and coefficient of determination). Data processing was carried out with the help of the SPSSversion 26 program. The results of the study show that Product Quality partially has a significanteffect on purchasing decisions by 81.3%, Price partially has a significant effect on PurchasingDecisions by 86.1% and there is a significant effect between the variables of Product Quality and Pricesimultaneously by 96.2% and the remaining 3.8% is influenced by other variables not examined inthis study.Keywords: Product Quality, Price, Purchase Decisions